Deployment status and common technical specifications for a B-PON system. - Ueda, H. (IEEE Communications magazine)
Broadband passive optical networks (B-PONs) have entered the commercial deployment phase in North America, Japan, and Europe. Nippon Telegraph and Telephone, BellSouth, France Telecom, British Telecommunications p.l.c., and SBC have developed a set of common technical specifications (CTS) for a B-PON system based on ITU-T Recommendations G.983.1, G.983.2 and G.983.3. They have deployed or plan to deploy B-PON systems based on this CTS. This article describes B-PON interface features, the outline of the CTS, and the deployment status of the B-PON systems around the world